Biomarkers Obtained by Transcranial Magnetic Stimulation of the Motor Cortex in Epilepsy - Tsuboyama, Melissa; Lee Kaye, Harper; Rotenberg, Alexander (Frontiers in Integrative Neuroscience, 2019)
Epilepsy is associated with numerous neurodevelopmental disorders. Transcranial magnetic stimulation (TMS) of the motor cortex coupled with electromyography (EMG) enables biomarkers that provide measures of cortical excitation and inhibition that are particularly relevant to epilepsy and related disorders. The motor threshold (MT), cortical silent period (CSP), short interval intracortical inhibition (SICI), intracortical facilitation (ICF), and long interval intracortical inhibition (LICI) are among TMS-derived metrics that are modulated by antiepileptic drugs. TMS may have a practical role in optimization of antiepileptic medication regimens, as studies demonstrate dose-dependent relationships between TMS metrics and acute medication administration. A close association between seizure freedom and normalization of cortical excitability with long-term antiepileptic drug use highlights a plausible utility of TMS in measures of anti-epileptic drug efficacy. Finally, TMS-derived biomarkers distinguish patients with various epilepsies from healthy controls, and thus may enable development of disorder-specific biomarkers and therapies both within and outside of the epilepsy realm.